Given

\(\displaystyle{x}-{y}=-{2}---{\left({1}\right)}\)

\(\displaystyle{3}{x}-{y}=-{2}---{\left({2}\right)}\)

From equation(1),we get the value of x in terms of y as

\(\displaystyle{x}-{y}=-{2}\)

\(\displaystyle{x}={y}=-{2}----{\left({3}\right)}\)

on substituting value of \(x=y-2\) from eq(3) to q(2),we get the value of y as

\(\displaystyle{3}{\left({y}-{2}\right)}-{y}=-{2}\)

\(\displaystyle{3}{y}-{6}-{y}=-{2}\)

\(\displaystyle{2}{y}={4}\)

\(\displaystyle{y}={2}\)

Now substitute value of \(y=2\) in eq(3),we get value of x as

\(\displaystyle{x}={2}-{2}\)

\(\displaystyle{x}={0}\)

Hence (0,2) is an ordered pair solution, not (1,3)